Challenges in the construction of a project in permanent education in health - Luiz Anildo Anacleto Silva; Daiane Michele Bonacina; Andressa de Andrade; Thanyze Carvalho de Oliveira (Universidade Federal de Santa Maria, 2012)
Objective: to meet the challenges in building a proposal for continue education in health in hospital institution. Method: the study is characterized as a qualitative, descriptive and exploratory. The study subjects were members of the multidisciplinary team. Results: the results indicate that, despite the difficulties to implement a proposal for institutional education, multidisciplinary team recognizes its importance to the highest professional qualification and qualification of care. Conclusion: the challenges included: overcoming the culture technicist education, bureaucracy and the payment of education in the work process